Semantic difficulties faced by students in China in understanding Arabic customs terms - Shuhan, Ma; Abdul Jabar, Mohd Azidan; Fang, Ng Chwee (Human Resource Management Academic Research Society, 2022)
To achieve the two objectives mentioned in the introduction, quantitative research methods were used in the advancement of research. A quiz was distributed to 60 students at two universities in northern China. However, Group B completed the quiz, which may increase the uncertainty of our result. We suggested the analysis using data collected from Group A that students accomplish the quiz within a limited time in their classes under the supervision of the author to obtain 30 samples. As for the quiz, it was composed of 10 Arabic customs terms, which were randomly selected from 30 Arabic customs terms in the glossary of the textbook. The overall result indicated that the average error rate for ten questions was about 50%, which means that every respondent had at least four questions on comprehension biases for Arabic customs terms through Chinese concepts. Furthermore, we adopted proper lexical and terminological semantics to examine the relationships between students’ answers and correct answers to find semantic difficulties. Meanwhile, we attempted to analyze the factors that influence students to have such problems. In this light, our study provides a model of learning of a subject terminology. And our study sheds on numerous semantic difficulties which would offer a steady stream of motivation for us to do a series of semantic studies in the future.